Medical expulsive therapy for the management of ureteric calculi - Shah, Yogendra D.; Thekdi, Pukur I.; Patel, K. G. (International Journal of Research in Medical Sciences, 2017)
Ureteric stones in endemic areas if treated on OPD basis with helps of oral drugs saves hospitalization and economic burden to the patient and the hospital. A prospective study was carried out for 9 and half years in two medical colleges by offering two different regimes to patients on random basis and regular follow-up was done on OPD basis. The stone passage rate was highest in the lower ureter 1/3rd (80%) followed by middle 1/3rd (45%) and upper 1/3rd (40%). The patients who were offered regime 1 which included diuretics had less success rate then that with regime 2 which included drugs like nifedipine and steroids. Treatment of ureteric stones on OPD basis in endemic areas is a boon for the patients and for the health management system in terms of cost and health care system.